ANALISIS FAKTOR SOSIAL EKONOMI DAN LINGKUNGAN TERHADAP KEJADIAN TUBERKULOSIS - Santoso, Raden Bagus Edy; Djafar, Tanwir; Sulistiyani, Sulistiyani; Pangaribuan, Resmi; Lellu, Amos (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2024)
Tuberculosis (TB) according to the World Heallth Orgalnizaltion (WHO) as the second deadly disease in the world in 2021 after Covid-19, and became the 13th (thirteen) as the main cause of death worldwide. Indonesia is ranked third in the world with the highest burden of TB cases after India and China. The trend of tuberculosis case finding rates for all types per 100,000 population in Lampung Province during 2016-2020 tends to increase. The purpose of the study was to determine the relationship of socioeconomic and environmental factors to the incidence of tuberculosis. The type of research was quantitative with a case control approach. The research was conducted in September-October 2023 at UPTD Puskesmas Tanjung Agung. The sample amounted to 58 respondents (29 case groups and 29 control groups). The sampling technique used purposive sampling. The research instrument consisted of a questionnaire sheet. The results showed that there was a relationship between economic status (p value: 0.009) and home hygiene (p value: 0.001). It is recommended that the Health Office carry out early detection of pulmonary tuberculosis problems routinely, in addition to carrying out preventive, promotive efforts in preventing pulmonary tuberculosis. The government, in this case the UPTD Puskesmas Tanjung Agung, conducts counseling about pulmonary tuberculosis and the dangers of smoking. The government also tries to implement programs to improve the economic status of the community as a priority or program.